Fixed Asset Intensity, Debt Ratio, and Effective Tax Rates: Evidence From Indonesian Energy Companies - Bella Putrie Nindyawan; Arif Nadzirul Haq; Arif Mahasin Sondani (Keizai, 2026)
This study evaluates the impact of fixed asset intensity and debt ratio on the effective tax rate (ETR), incorporating firm size as a control variable. The primary focus is to examine tax management strategies through the optimization of asset and financing structures to reduce the real tax burden. Employing a quantitative method with multiple linear regression analysis, this research observes 96 data points from 32 energy sector companies for the 2022–2024 period, selected through purposive sampling. The findings indicate that fixed asset intensity has a significant negative effect on the ETR due to the role of depreciation expenses as a tax shield. Conversely, the debt ratio has no significant effect, suggesting that debt levels are not the primary determinant of the tax burden within this sample. With an Adjusted R-Square value of 30.1%, this model provides insights for management regarding asset administration and for tax authorities concerning the fiscal characteristics of capital-intensive industries.